Bahan Ajar Digital Berbasis Multiaplikasi Mata Pelajaran IPAS SD - Achmad Fanani; Cholifah Tur Rosidah; Triman Juniarso; Gresya Ailina Roys; Eldine Salsabila Putri; Vannilia Vannilia; Achmad Fanani; Cholifah Tur Rosidah; Triman Juniarso; Gresya Ailina Roys; Eldine Salsabila Putri (Universitas Negeri Malang, 2022)
Abstract: IPAS is a new subject in the Merdeka curriculum, a combination of Natural and Social Sciences. It takes the availability of teaching materials as an alternative choice, so that it is possible to support the science learning process to be more fun, practical, and interesting. The problem in this research is how the product form of Digital Teaching Materials Based on Multi-Application Science Materials for Elementary School. This type of research includes development research using a 4-D model design. Development of digital teaching materials using several applications including Google site, Flipbook, Canva, Mentimeter, PowerPoint, Google Form, Life Work Sheet, and X-Mind. The results of this study are expected to be used as examples and descriptions of teaching materials for teachers and prospective teacher students in planning and developing learning, especially related to the integrated blending of content (learning materials and setting experiences, assignments and steps for more effective learning activities according to learning objectives). Abstrak: IPAS merupakan mata pelajaran baru dalam kurikulum Merdeka gabungan Ilmu Pengetahuan Alam dan Sosial. Dibutuhkan ketersediaan bahan ajar sebagai alternatif pilihan, sehingga memungkinkan dapat mendukung proses pembelajaran IPAS lebih menyenangkan, praktis, dan menarik. Masalah dalam penelitian ini yaitu Bagaimana wujud produk Bahan Ajar Digital Berbasis Multi Aplikasi Mata Pelajaran IPAS SD. Jenis penelitian ini termasuk penelitian pengembangan dengan menggunakan rancangan model 4-D. Pengembangan bahan ajar digital menggunakan beberapa aplikasi diantaranya Google site, Flipbook, Canva, Mentimeter, Power Point, Google Form, Life Work Sheet, dan X-Mind. Hasil penelitian ini diharapkan dapat dijadikan contoh dan gambaran bahan ajar guru dan mahasiswa calon guru dalam merencanakan dan mengembangkan pembelajaran terutama terkait dengan meramu secara terintegeratif antara isi (materi pembelajaran dan penetapan pengalamann, tugas dan Langkah-langkah aktivitas pembelajaran lebih efektif sesuai tujuan pembelajaran).